The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1167/iovs.15-18991
|View full text |Cite
|
Sign up to set email alerts
|

The Appearance of Phosphenes Elicited Using a Suprachoroidal Retinal Prosthesis

Abstract: Citation: Sinclair NC, Shivdasani MN, Perera T, et al.; for the Bionic Vision Australia Consortium. The appearance of phosphenes elicited using a suprachoroidal retinal prosthesis. Invest Ophthalmol Vis Sci. 2016;57:4948-4961. DOI:10.1167/ iovs.15-18991 PURPOSE. Phosphenes are the fundamental building blocks for presenting meaningful visual information to the visually impaired using a bionic eye device. The aim of this study was to characterize the size, shape, and location of phosphenes elicited using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
75
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 49 publications
6
75
1
1
Order By: Relevance
“…Our group, through the Bionic Vision Australia program, has been working on placing an electrode array between the sclera and the choroid, thus using a suprachoroidal approach. [2][3][4][5] While each anatomical location provides unique advantages, the potential benefits of using the suprachoroidal location are the ease of surgical implantation of the electrode array, mechanical stability in situ over the long term, the ability to cover a large area of the visual field, and minimal risk of retinal trauma. event.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Our group, through the Bionic Vision Australia program, has been working on placing an electrode array between the sclera and the choroid, thus using a suprachoroidal approach. [2][3][4][5] While each anatomical location provides unique advantages, the potential benefits of using the suprachoroidal location are the ease of surgical implantation of the electrode array, mechanical stability in situ over the long term, the ability to cover a large area of the visual field, and minimal risk of retinal trauma. event.…”
Section: Purposementioning
confidence: 99%
“…event. 2 Reliable phosphene thresholds could be measured in all patients, and the most effective stimulus parameters 3 and individual phosphene characteristics 5 were determined through extensive psychophysical studies using single-electrode stimulation. Using a camera-based semiportable system along with head scanning, patients were able to recognize simple shapes and objects, and data from one patient showed that the implant was capable of providing measureable visual acuity on an optotype acuity task.…”
Section: Purposementioning
confidence: 99%
“…Retinal prostheses are based on this principle. Retinal prostheses are classified into four types, depending on the position of the electrode array: (1) epiretinal (placed on the retina from the vitreous side), (5) (2) subretinal (placed between the choroid and the retina), (7) (3) placed between the choroid and retinal pigment epithelium, (8) and (4) placed in the sclera. (9) We have been developing a retinal prosthesis based on suprachoroidal transretinal stimulation (STS) in which the electrode array is placed in a scleral pocket created by making a half-layer incision.…”
Section: Introductionmentioning
confidence: 99%
“…For example, biphasic rectangular current pulses are used in epiretinal, (5) suprachoroidal, (8) and STS prostheses. (9,11) Charge-balanced biphasic pulses can carry out electrical stimulation safely without causing damage to tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore entirely plausible that results achieved in the retina may not fully translate into perceptual outcomes as some of the perceptual distortion of phosphenes could be caused by central mechanisms and plasticity associated with long-term blindness (24). Finally, the perceptual benefits achieved with long phase durations may only apply to patients implanted with an epiretinal prosthesis, as perceptual distortions shown to be a result of axonal activation has not primarily been observed with subretinal (2) or suprachoroidal (25,26) stimulation.…”
mentioning
confidence: 99%